Duloxetine Treatment of Stress Urinary Incontinence in Women Does Not Induce Mania or Hypomania - Viktrup, Lars (Physicians Postgraduate Press, Inc., 2004)
Background: Mania is a rare but unwelcome side effect of treating depressed patients with antidepressants. This research sought to determine the risk of treatment-emergent mania or hypomania in women with stress urinary incontinence treated with duloxetine, a balanced dual serotonin-norepinephrine reuptake inhibitor currently under investigation for the treatment of both stress urinary incontinence and major depressive disorder. Method: Data were obtained from 4 double-blind, randomized, placebo-controlled studies involving 1913 women aged 22 to 83 years and 4 ongoing uncontrolled longer-term studies involving 1877 women aged 20 to 87 years. In all studies, women had the predominant symptom of stress urinary incontinence; in the active treatment arms, all women received duloxetine 80 mg/day. Women receiving antidepressants for major depressive disorder were excluded. In the placebo-controlled studies, 1 woman reported a history of bipolar disorder and 74 women reported a history of depression. In the uncontrolled longer-term studies, 1 woman reported a history of bipolar disorder and 69 reported a history of depression. Results: In the placebo-controlled trials, 1 woman treated with duloxetine reported euphoria, while 1 reported mania and 1 reported euphoria when on placebo. In the uncontrolled longer-term studies, 1 woman reported mania; 1, euphoria; and 4, elevated moods. No women discontinued the study due to treatment-emergent mood elevation. Conclusion: These data suggest that duloxetine does not induce mania or hypomania in women with stress urinary incontinence in this population, in which few women had a history of bipolar disorder or depression and women on antidepressants were excluded.